(untitled) (Journal of Philosophy Culture and Political Science, 2024)
This article is based on the results of the research conducted in 2023, implemented under the agreement between the Hanns Seidel Foundation and the Academy of Public Administration under the President of the Republic of Kazakhstan. This study is a logical continuation of the research conducted in 2021 on satisfaction of local heads (akims) with the first conducted elections of akims of cities of district significance, rural districts, settlements and villages. The researchers assume that newly elected local heads may have problems with decision-making on some issues. This may be provoked by the lack of certain competences needed in rural areas. The article presents the results of the research of training needs of representatives of local government. During the research a mixed type of methods (quantitative and qualitative) was used. At the first stage, a sociological survey was conducted among local heads (akims) of cities of district significance, rural districts, settlements and villages (n=250). At the second stage of the research an in-depth interview was conducted with participation of akims, representatives of non-governmental organisations and business structures (n=29). The study showed that there is a need for training in communication skills, financial and legal literacy, as well as socio-cultural and psychological competences among representatives of local government. Keywords: public administration, local government, public service, local executive bodies, professional competencies, education, public policy, training.